Providing for pollinators: conserving and integrating natural habitats to support pollinator conservation efforts - Butters, Jessica Nicole (Kansas State University, 2021)
Pollinators have been in decline for at least the past four decades due to habitat loss from agricultural intensification. Natural pollinator habitat, such as tallgrass prairies, have shrunk to less than 10% of their original extent. Because over one-third of food crops are completely pollinator-dependent, we are under the threat of food instability if pollinator decline is not stabilized and improved. Additionally, little work has been done in terms of understanding how different land management strategies, such as fire rotations or native flower plantings, impact different groups of pollinators, such as bees and butterflies. In an effort to address these issues, I implemented a two-year study on the impact of conservation and ecological intensification strategies on pollinators. My objectives were to 1) understand how fire and grazing management on a prairie reserve impacts the pollinator community and 2) examine how land managers can attract and provide for pollinators in an agricultural setting through the implementation of perennial border crops. For my first objective, I found that bison grazing had positive effects on nearly all pollinators, from lepidopterans to ground-nesting bees, while different fire rotations had both positive and negative effects on pollinators through different pathways. I also found that both fire and grazing had significant impacts on pollinator habitat, such as soil characteristics and forb species richness. In an agricultural setting, I found that pollinators in general were most attracted to diverse, flowering border crops such as prairie mixes, as well as native sunflower species planted in a monoculture. Besides crop treatment, we also found that “year” had a significant impact on pollinators, indicating that establishment periods of crops need to be taken into consideration. These findings offer valuable insight into the impacts of different land management strategies on different pollinator groups, and provide landowners such as farmers and restoration biologists, more information about how their management practices may affect specific pollinator groups.
Keywords: Pollinators; Tallgrass Prairie; Conservation; Sustainable Agriculture; Border Crops; Hedgerows